Trade Liberalization and Gender Inequality - Juhn, Chinhui; Ujhelyi, Gergely; Villegas-Sanchez, Carolina (American Economic Review, 2013)
We consider a model where firms differ in their productivity and workers are differentiated by skill and gender. A reduction in tariffs induces more productive firms to modernize their technology and enter the export market. New technologies involve computerized production processes and lower the need for physically demanding skills. As a result, the relative wage and employment of women improves in blue-collar tasks, but not in white-collar tasks. We empirically confirm these theoretical predictions using a panel of Mexican establishments and the tariff reductions associated with the North American Free Trade Agreement (NAFTA).